2019
DOI: 10.1007/s12220-019-00210-6
|View full text |Cite
|
Sign up to set email alerts
|

The Hitchin–Kobayashi Correspondence for Quiver Bundles over Generalized Kähler Manifolds

Abstract: In this paper, we establish the Hitchin-Kobayashi correspondence for the I±-holomorphic quiver bundle E = (E, φ) over a compact generalized Kähler manifold (X, I+, I−, g, b) such that g is Gauduchon with respect to both I+ and I−, namely E is (α, σ, τ )-polystable if and only if E admits an (α, σ, τ )-Hermitian-Einstein metric.where ·, · denotes the natural inner product on T X ⊕ T * X. Definition 2.2. ([12]) A manifold X is called a generalized Kähler manifold if it carries the data (I + , I − , g, b), where•… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Leveraging the elliptic regularity, we can deduce that there exists a subsequence H v (t) converging to H v,∞ in the C ∞ loc -topology. Applying (24), we recognize that H v,∞ is the desired metric that satisfies the boundary condition. Finally, the uniqueness is guaranteed by the maximum principle and Proposition 3.…”
Section: Finding Solutions To the Perturbed Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Leveraging the elliptic regularity, we can deduce that there exists a subsequence H v (t) converging to H v,∞ in the C ∞ loc -topology. Applying (24), we recognize that H v,∞ is the desired metric that satisfies the boundary condition. Finally, the uniqueness is guaranteed by the maximum principle and Proposition 3.…”
Section: Finding Solutions To the Perturbed Equationmentioning
confidence: 99%
“…Later, Zhang [23] generalized their results to the compact almost-Hermitian manifold. Recently, the DUY theorem for quiver bundles has been extensively studied by Hu and Huang [24] to the compact generalized Kähler manifold. In summary, they showed that the stability of the holomorphic quiver bundle and the existence of Hermite-Yang-Mills metric over some compact Hermitian manifolds are equivalent.…”
Section: Introductionmentioning
confidence: 99%